Penapisan Kapang Asal Lahan Sulfat Masam Kalimantan Selatan Sebagai Penghasil Enzim Ekstraseluler - Dwi Ningsih Susilowati; Indah Sofiana; Kristina Dwi Atmini; Erny Yuniarti (Agric, 2020)
Kalimantan acid sulphate land has the potential to be developed into productive land, with good land optimization. Utilization of rhizosphere microorganism diversity, especially mold can potentially provide a solution in optimizing agricultural land, namely the ability to produce extracellular enzymes. This study aims to determine the potential of mold originating from acid sulphate fields in producing extracellular enzymes (pectinase, chitinase, glucanase, cellulase, and phosphatase). The study was conducted in June-July 2019 at the Microbiology Laboratory, Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development. Screening  of extracellular enzyme-producing fungi was carried out on selection media. The results obtained by some isolates have the ability to produce extracellular enzymes. Indications of the ability of mold to produce extracellular enzymes are the presence of clear zones in the selection medium. In pectinase, chitinase and glucanase testing all isolates showed negative results. Potential isolates in producing extracellular enzymes include Penicillium sp. Paddy 4.1 (cellulolytic index 2.43),  Clonostachys sp. KRMT 17.9 and Penicillium singorense KLK 13.7 (proteolytic indices 3.97 and 3,00, respectively). The difference in index values ​​indicates the variation in the level of enzyme activity.